Pengaruh Kompetensi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan PT. Borneo Lintas Dunia - Desiana Dian Malasari; Desta Ovilini (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid growth of the travel service industry reflects increasing public demand for transportation and tourism services that are practical, safe, and reliable. This development encourages travel agencies to continuously improve employee competence and service quality to enhance customer satisfaction and remain competitive. PT. Borneo Lintas Dunia, a travel service company providing airline ticketing and domestic and international tour packages, seeks to deliver safe, comfortable, and professional travel experiences by strengthening human resource competence and improving service quality. This study used a quantitative approach to examine the causal relationship between employee competence, service quality, and customer satisfaction at PT. Borneo Lintas Dunia. Data were collected through questionnaires distributed to customers as primary data, while secondary data were obtained from relevant documents and supporting sources. The quantitative method was applied to measure the influence of employee competence and service quality as independent variables on customer satisfaction as the dependent variable. The results show that employee competence has a positive and significant effect on customer satisfaction, as higher levels of employee knowledge and skills improve customer perceptions. Service quality also significantly influences customer satisfaction, where reliability, responsiveness, and service accuracy increase customer satisfaction levels. Therefore, improving employee competence and maintaining high service quality are important strategies to enhance customer satisfaction and sustain competitiveness in the travel service industry.